FACTORS THAT INFLUENCE SMES' PERCEPTIONS ABOUT THE IMPORTANCE OF PREPARING FINANCIAL STATEMENTS (CASE STUDY AT A BICYCLE SHOP IN SURAKARTA AND SUKOHARJO) - Rukmini Rukmini; LMS Kristiyanti; M Fachri Naufal Barokah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Various problems that are still faced by Micro, Small and Medium Enterprises (MSMB) are in utilizing the use of financial statements. The inability to practice accounting is the main factor that causes problems and triggers MSMB failure in developing their business. This study aims to determine: (1) the effect of business size on MSMB perception on the importance of financial statement preparation, (2) the effect of time on MSMB perception on the importance of financial reporting, (3) the influence of educational background on MSMB's perception of the importance of preparing financial statements, (4) the effect of business size, length of business, educational background on MSMB's perception on the importance of preparing financial statements. The results of this study indicate that (1) there is no positive effect on the scale of the company on the use of accounting information. Evidenced by a regression coefficient of 0.222, the value of t is greater than t table 1.258, and the significance value is 0.210 (0.210> 0.05). (2) there is a positive influence of accounting knowledge on the use of accounting information. Evidenced by a regression coefficient of 0.188, the value of t is greater than t table 4.629, and significant value of 0.000 (0.000